Role of green finance in sustainable energy transition and economic growth in MENA region - Gafsi, Nesrine; LOUHICHI, Leila (Edelweiss Applied Science and Technology, 2025)
This study examines the inter-dynamics between green finance, sustainable energy change, and economic development in the emerging MENA economies. Applying the Autoregressive Distributed Lag (ARDL) bounds test approach, it estimates panel data of chosen countries over the period 2010-2023 to analyze short- and long-term effects. Empirical results confirm a long-term cointegration relationship among the variables, and green finance and renewable energy consumption are positively and statistically significantly related to GDP. Granger causality tests also support bidirectional causality between green finance and economic development, and unidirectional causality from green finance to sustainable energy transition. The results confirm the instrumental role of green finance in underpinning low-carbon energy infrastructure and long-term economic development. The report concludes by mentioning policy measures needed to scale up green financial products in the region, including green bonds, ESG investments, and regulation overhaul. Implications include converging fiscal and energy policies to mobilize blended finance for clean energy projects, enhancing investor trust, and supporting sustainable development. This paper contributes to the emerging green macro-financial linkages literature and offers policy suggestions for MENA policymakers interested in balancing economic development and environmental protection.